CHEMISTRY IN PRIMO LEVI?S LITERATURE: PHILOSOPHICAL ASPECTS ON EXPERIMENTATION, MATTER AND THE PROFESSION OF CHEMISTRY - Valero, Rafaela [UNESP]; Mori, Rafael C.; Massi, Luciana [UNESP] (Soc Brasileira Quimica, 2023)
The Italian chemist Primo Levi (1919-1987) published a testimonial literature about the period he was captive in Auschwitz, later exploring other literary genres. In his work as a whole, the science-art relationship takes place both in terms of content (when chemistry and scientific knowledge are themes) and form (when the author appropriates the language and logic of science to communicate his experiences, especially those lived in the concentration camp). Three themes related to the chemical universe are present in Levi's writings: experiments, man's relationship with matter and chemistry as a work. In this article, we bring these topics closer to current discussions in the field of philosophy of chemistry. The philosophical discussion and Primo Levi's literature converge on the understanding that experiments assumes a particular role in chemistry, that matter is a central category for this science and that the chemical profession raises ethical questions, such as those related to impacts of the incessant production of new substances.
Keywords: Primo Levi; literature; philosophy of chemistry